Fertilización química y orgánica en dos variedades de arroz (Oriza sativa) en la zona de Daule. - García Navarrete, Tubal Gastón (2011)
This research was conducted at km. Guayaquil road 47 - Balzar, Campus Independence, Coloma sector, belonging to the canton Daule. Geographic Coordinates: Latitude: S17 ° 0 'and Longitude: W 84 ° 0'. The site topography is flat with a clay loam soil type, the duration of the lock 2011.las weather conditions in the area. Temperature 25.4 ° C. 75.0% relative humidity. 997.5 heliophany hours light years. Precipitation is 1587.5 mm / year. Mm./años3.0 average annual evaporation. Height 3.0 m. Factors studied: Factor A, varieties of rice, INIAP-11, 2INIAP-14 and Factor B, organic and chemical fertilizers, Biocompost, 45 L/ha-1. Tn/ha-1 Ecoabonaza 2. Fertilizer (8-20-20) 150 kg/ha-1. Urea Fertilizer, 180 kg/ha-1. The two varieties of rice and organic fertilizers and the two chemical fertilizers, we get the following treatments: 11 + Biocompost INIAP 45 L/ha-1. 11 + 2 INIAP Ecoabonaza tn/ha-1. 11 + Fertilizer urea180 INIAP kg/ha-1. INIAP 11 + 150 kg/ha-1 8-20-20 fertilizer. 14 + Biocompost INIAP 45 L/ha-1. 14 + 2 INIAP Ecoabonaza tn/ha-1. 14 + Fertilizer urea180 INIAP kg/ha-1. INIAP 14 + 150 kg/ha-1 8-20-20 fertilizer. In the present study used a factorial 2 x 4, arranged in a Complete Block Design Randomized (RCBD) with 3 replications. For the analysis of means was applied multiple range test of Tukey (P <0.05 and P = 0.01). The height of plant experimental measurements 15, 30, 45, 60 days, tillering 15, 30, 45, and 60 days, panicle length, grain number per panicle, number of spikes per m2, grain length, Performance and Analysis economic. The results of two rice varieties and INIAP INIAP-11-14, with chemical fertilizer and organic manures evaluated variables were not statistically different. The greatest response in wet and dry performance 10745.21 and 9842.80 lbs ha-1.In the INIAP-11, plant height and length 87.73 cm 08.09 cm grain. While the best response ecoabonaza fertilization on number of grains per panicle 127.33. Grain length 9.15 cm and in fertilizers and fertilizer per hectare yield wet and dry lbs/ha-1 11011.36 and 10136.36. According to the best combination treatments rice variety INIAP-11 with 2 tn/ha-1 ecoabonaza fertilization and 8-20-20 150 kg/ha-1 to 11128.64 and 10212.12 lbs/ha-1.